Willingness of Chinese households to pay extra for hydrogen-fuelled buses: A survey based on willingness to pay - Wang, Shuai; Tan, Yang; Fukuda, Hiroatsu; Gao, Weijun (Frontiers in Environmental Science, 2023)
Hydrogen-fuelled buses play an important role in the construction of low-carbon cities as a means of green travel. Beijing, as a pilot city of hydrogen-fuelled buses in China, is very important in the promotion of hydrogen-fuelled buses in China. Unfortunately,, the public acceptance of hydrogen-fuelledfuelled buses and their environmental positive externality value have not been studied. In this paper, we investigated the willingness of Beijing households to pay for the promotion of hydrogen-fuelled buses and its influencing factors by means of a web-based questionnaire. The spike model was also used to estimate the willingness to pay (WTP) for hydrogen buses. The results show that the WTP of Beijing households is CNY 3.19 per trip. The value of a positive environmental externality is approximately CNY 29.15 million per trip. Household income level, environmental knowledge, individual environmental ethics, and perceived behavioural control are the main influencing factors of WTP. Therefore, policy-makers should strengthen publicity efforts to increase individuals' environmental awareness and environmental ethics and optimize the layout of hydrogen-fuelled bus schedules and riding experiences to improve individuals' perceptual and behaviour control. Finally, the positive environmental externality value of hydrogen buses should be valued, which will help increase investor interest.